Novel design and applications of robotics technologies - Zhang, Dan, 1964-; Wei, Bin, 1987- (Advances in computational intelligence and robotics (ACIR) book series., 2019)
"This book explores novel design concepts, analysis and synthesis, and many application fields. It also covers emerging fields that include: mathematical and computational methodologies in robotics, healthcare robotics, social robotics, manufacturing robotics, human-robot interaction, bio-inspired robotics, control algorithms, and control systems"--